(untitled) (Research, Society and Development, 2020)
The present work had as objective to verify the adhesion of the Program of Feeding of the Worker in the companies before and after the Interministerial Ordinance of n° 66 of August 25, 2006, in relation to the alterations in the nutritional value of the menus, fulfillment of this and its impact in the worker’s health. It is an integrative literature review, of exploratory character, with qualitative approach, carried through in the months of January to October of 2019. The findings of the present study showed that the companies registered in PAT do not follow the nutritional parameters determined before and after the inter-ministerial ordinance of No. 66 of August 25, 2006, because the evaluated works highlighted there is incidence of overweight and obesity among the workers who are benefited by the program.